Does Cervical Sagittal Balance Affect the Preoperative Neck Disability Index in Patients With Cervical Myelopathy?. Issue 1 (February 2020) - Lin, Taotao; Chen, Penghong; Wang, Zhenyu; Chen, Gang; Liu, Wenge
Abstract : Study Design: This was a retrospective study. Objective: This study aimed to ascertain the relationship between preoperative Neck Disability Index (NDI) scores and cervical sagittal alignment in patients with cervical spondylotic myelopathy (CSM). Summary of Background Data: Cervical alignment may influence postoperative clinical outcomes. However, the effect of preoperative sagittal balance on the preoperative status in CSM patients remains uncertain. Materials and Methods: From 2010 to 2016, 90 patients who underwent cervical surgery for CSM were enrolled. The inclusion criteria for this study included preoperative standing cervical radiographs and a preoperative NDI score. The following radiographic parameters were measured: (1) C0–C2 lordosis, (2) C2–C7 lordosis, (3) C2–C7 sagittal vertical axis (SVA), (4) neck tilt, (5) thoracic inlet angle, (6) T1 slope, and (7) T1 slope minus cervical lordosis (T1S-CL). The Pearson product-moment correlation coefficients were calculated between all radiographic variables and the NDI scores, and multiple regression analysis was performed to determine the independent predictors of high preoperative NDI scores. Results: Both C2–C7 SVA and T1S-CL were positively correlated with NDI scores ( r =0.732, P <0.001 and r =0.333, P =0.001). Cervical lordosis was negatively correlated with NDI scores ( r =−0.267, P =0.011). Significant correlations were found between C2–C7 SVA and the C0–C2 Cobb angle ( r =0.244, P =0.020), C2–C7 SVA and the C2–C7 Cobb angle ( r =−0.359, P =0.001), the C2–C7 Cobb angle and the C0–C2 Cobb angle ( r =−0.457, P <0.001), and the C2–C7 Cobb angle and T1 slope ( r =−0.385, P <0.001). Conclusions: The disability of the neck increased with increasing C2–C7 SVA and T1S-CL and decreasing cervical lordosis before surgical reconstruction. High C2–C7 SVA, low thoracic inlet angle, and high neck tilt values are independent predictors of high preoperative NDI scores.